Characteristics and effect of 8-week soccer training on lactate minimum speed - Campos, E. Z.; Zagatto, A. M.; Nakamura, F. Y. (Sport Sciences for Health, 2016)
Purpose: This study aimed to (1) characterize 8 weeks of specific soccer training according to heart rate (HR) zones and speed zones, and (2) verify the effects of 8 weeks of specific soccer training on lactate minimum speed (LMS), and the respective HR (HRLMS) of professional soccer players. Methods: Fourteen professional soccer players (23 [3] years old, 78.4 [7.0] kg, and 6.9 [2.4] % body fat; second national division) underwent a lactate minimum test at two different moments, before and after 8 weeks of specific training. The training was characterized according to time spent at each heart rate zone, and in different speed zones. The comparison between LMS and HRLMS was performed using the Wilcoxon test. An effect-size qualitative analysis was also performed. Results: The training was performed predominantly in zone 1 (<80 % of maximal HR). The time spent at velocities below mean LMS was predominant. The LMS (pre: 10.9 [0.8] km h-1; post: 11.8 [0.7] km h-1), and its corresponding heart rate (pre: 161 [7.0] bpm; post: 163 [9.0] bpm) did not differ significantly between pre and post-training. However, the effect size analysis showed a moderate effect on LMS. Conclusion: Eight weeks of soccer training slightly increased LMS, without changing HRMLS. Since LMS heart rate does not change with training, it can be used as a boundary of soccer training intensity (i.e., above or below anaerobic threshold).